Artificial intelligence for capital markets - Hasan Jafar, Syed (CRC Press, 2023)
Artificial Intelligence for Capital Market throws light on the application of AI/ML techniques in the financial capital markets. This book discusses the challenges posed by the AI/ML techniques as these are prone to "black box" syndrome. The complexity of understanding the underlying dynamics for results generated by these methods is one of the major concerns which is highlighted in this book.Features:- Showcases artificial intelligence in finance service industry- Explains credit and risk analysis- Elaborates on cryptocurrencies and blockchain technology- Focuses on the optimal choice of asset pricing model- Introduces testing of market efficiency and forecasting in the Indian stock marketThis book serves as a reference book for academicians, industry professionals, traders, finance managers and stock brokers. It may also be used as textbook for graduate level courses in financial services and financial analytics
Keywords: bicssc / Data mining; bicssc / Computer architecture & logic design; bicssc / Supercomputers; bicssc / Automatic control engineering; bisacsh / COMPUTERS / Programming / Games; bisacsh / COMPUTERS / Computer Science; bisacsh / COMPUTERS / Data Science / Data Analytics; bisacsh / COMPUTERS / Machine Theory; bisacsh / COMPUTERS / Data Science / Neural Networks; Aufsatzsammlung